The influence of 18Cr10NiTi and ODS 18Cr10NiTi austenitic stainless steels microstructure on the deuterium desorption - Kalchenko, A.S.; Ruzhytskyi, V.V.; Karpov, S.A.; Kolodiy, I.V.; Tikhonovsky, M.A.; Tolstolutskaya, G.D.; Velikodnyi, A.N.; Voyevodin, V.N. (Вопросы атомной науки и техники, 2020)
The thermal desorption spectra of deuterium from 18Cr10NiTi and ODS 18Cr10NiTi steel specimens irradiated with 10 keV D₂⁺ ions were examined. The influence of radiation damage on microstructure and accumulation of deuterium implanted in steels at room temperature and after annealing have been studied. Thermal desorption spectrum (TDS) from a specimen of ODS 18Cr10NiTi steel exhibits deuterium release over a wide temperature range with two well–defined maxima at ~ 420 and ~ 970 K. Two types of precipitates – oxides (Y–Ti–O) and carbides TiC are considered to explain the mechanism of the deuterium trapping to high annealing temperatures. Досліджено спектри термодесорбції дейтерію із зразків сталей Х18Н10Т і Х18Н10Т ДЗО, опромінених іонами 10 кеВ D₂⁺. Вивчено вплив радіаційних пошкоджень на мікроструктуру і накопичення дейтерію після його імплантації в сталі при кімнатній температурі і після відпалу. Спектр термодесорбції зі сталі Х18Н10Т ДЗО демонструє виділення дейтерію в широкому інтервалі температур з двома максимумами при ~ 420 і ~ 970 К. Розглянуто два типи преципітатів – оксиди (Y–Ti–O) і карбіди (TiC) для пояснення механізму утримання дейтерію до високих температур відпалу. Исследованы спектры термодесорбции дейтерия из образцов сталей Х18Н10Т и Х18Н10Т ДУО, облученных ионами 10 кэВ D₂⁺. Изучено влияние радиационных повреждений на микроструктуру и накопление дейтерия после его имплантации в стали при комнатной температуре и после отжига. Спектр термодесорбции из стали Х18Н10Т ДУО демонстрирует выделение дейтерия в широком интервале температур с двумя максимумами при ~ 420 и ~ 970 К. Рассмотрены два типа преципитатов – оксиды (Y–Ti–O) и карбиды (TiC) для объяснения механизма удержания дейтерия до высоких температур отжига.